Evaluation of the Occurrence of Initial Failures from Stress Concentrators in Welded Joints and Structural Elements - K. А. Molokov; V. V. Novikov; M. Dabalez (Advanced Engineering Research, 2023)
Introduction. Data on the occurrence of initial failures obtained through testing on standard samples cannot always be extrapolated to real welded joints and structures. This is due to the difference between the concentrators in the joints, because after welding there is a significant structural and mechanical heterogeneity of the heat-affected and stress concentrator zone. Extended, deep concentrators are considered as crack-like defects, at whose vertices a volumetric, multiaxial stress state is formed. The paper addresses the issue of constructing critical diagrams of the onset of the limiting state at the concentrator vertex, which depends on the level of external load and the theoretical concentration coefficient.Materials and Methods. Analytical methods were used to study the stress state. The literature on the topic was analyzed. The features of proven physical models and patterns of behavior of materials were taken into account. The characteristics of steel alloys were taken from open sources and summarized in a tabulated form. Nonlinear equations were solved in Matlab applications. The diagrams constructed by the authors enable to track the correlation of the dangerous level of the theoretical stress concentration factor and the level of external load. Curve Fitting Toolbox Matlab was used to design the graphic part of the work.Results. The characteristic of damage from stress concentrators in welded joints was given. The crack propagation in the fusion zone was shown. The conditions stimulating and inhibiting destruction were indicated. The theoretical stress concentration factor α𝑇 was specified. It was shown how this indicator depended on the width, the height of the seam and the thickness of the welded part. Acute stress concentrators with theoretical concentration factor αт= 5…14 and more were studied. For this case, an approximating formula was given that took into account the maximum stress in the concentrator in the first half cycle, the initial deformation, and the load ratio. Through those elements, an indicator of an increase in maximum stresses was set depending on the number of loading cycles. The flow condition, the stress state, and the overvoltage factor, which took into account the increase in the first principal voltage for a combined stress state, were analytically shown. A model of the critical state at the apex of an acute stress macro concentrator was described. It was presented as the dependence of the relative stresses of the initiation of destruction σн𝑏𝑐/σ0,2 on the concentrator. Possible variations of this model were analyzed. The dependences of relative values σ𝐻𝑏𝑐⁄σ0,2 on the theoretical concentration factor α𝑇𝑏𝑐=α𝑇 were presented. To check the physical adequacy of this model, graphs were constructed that reflected changes in the relative stress of the external load at a critical state at the stress concentrator apex. The inevitability of bifurcation as a result of the studied processes was validated. Two directions of further development of events were indicated: brittle destruction and loss of stability of the stressed state with the transition to an increase in plastic deformations. The moment of bifurcation was defined as a critical state in the focus of the concentrator.Discussion and Conclusion. The analysis and calculations performed within the framework of the presented scientific work enabled, in particular, to draw conclusions about the role of key factors of the processes under study. It was established, for example, that the operation of a steel alloy at a high theoretical stress concentration factor depended on the characteristics of the stress state. In a rigid state, it was possible to inhibit shear deformation and the onset of the limiting state at a lower value of the theoretical stress concentration factor. With the usual strength of steel (in comparison to high), a greater impact of the volume of the stress state on the value of the theoretical stress concentration factor was recorded. The probability of failure depended on the resistance of the material to the growth of a macrocrack. In future research, it is possible to refine analytical models and results, evaluate effective stress concentration factors.